Epidemiology of Helicobacter Pylori in three districts of Sabah - Murtaza Mustafa (Universiti Malaysia Sabah, 2012)
Background and Aims-Recent studies have shown that Helicobacter pylori infection proved to be of great public health importance in the developing countries and developed countries, especially in low socioeconomic groups. Poor hygiene suboptimal sanitation and crowded conditions; have been reported as risk factors. The aim of the study was to investigate the seroepidemiology of H. pylori infection in the three districts of Sabah e.g. Kota Kinabalu ,KotaMarudu and Kudat. The cross sectional study describes the prevalence of infection with H. pylori as determined by a serodiagnostic assay. A prevalence of (32.26 %) in 1156 Subjects, in age groups 12 to 80 years from three districts, using a common protocol for blood collection and serological testing. In all populations combined, the prevalence of infection was higher in the ethnic Kadazan community (76.%) compared with Malay ,Bajau (14 %) community. Infection was higher (59 % ) in the women than in men (41 %).Lower income groups had significantly higher prevalence (76.4 %).Older age groups had higher infection (42.75 %) than the younger age groups. Subjects with higher education had lower levels of infection (27.9 %) compared with subjects with education up to primary education (36.2 %),groups with secondary education, (17.35 % ),subjects with no education (18.6 %).Increasing prevalence of infection in subjects with increaSing body mass indexed (44.1 %), compared with normal weight (35.8%). There was considerable effect of smoking and alcohol consumption on the prevalence of infection. Former smokers had infection (79.8 %) compared to current smokers (5.9 %).Former alcohol consumers had infection (79.7 %) compared to no-alcohol consumer (14.2 % ).There was considerably variation in the prevalence of infection between rural and urban populations but, within populations ethnicity ,socioeconomics and low education standard was consistently associated with prevalence of infection.